Set membership estimation of parameters and variables in dynamic networks by recursive algorithms with a moving measurement window - Duzinkiewicz, Kazimierz (Zielona Góra: Uniwersytet Zielonogórski)
The paper considers a set membership joint estimation of variables and parameters in complex dynamic networks based on parametric uncertain models and limited hard measurements. A recursive estimation algorithm with a moving measurement window is derived that is suitable for on-line network monitoring.
Keywords: set membership estimation; uncertainty; complexity; networks; water distribution